Universal quantum obfuscation for quantum non-linear functions - Pan, Chuyue; Shang, Tao; Zhang , Yuanjing (Frontiers in Physics, 2023)
The research of quantum cryptography has burgeoned in the recent decades and combined quantum mechanics and cryptography theory. Among the existing quantum cryptographic primitives, quantum obfuscation is an emergent force to be reckoned with. Quantum obfuscation means obfuscating a circuit by quantum mechanics to improve security. It is used to hide functionality and prevent the reverse engineering of quantum circuits. However, researches on the construction of quantum obfuscation are relatively immature due to its difficulty in implementation and application. And the obfuscation for quantum nonlinear functions has not been suggested yet although quantum nonlinear functions cover a wide range of quantum functions that can be obfuscated. In this paper, we initiate a universal definition of quantum obfuscation which utilizes quantum teleportation to construct obfuscator and interpreter for quantum nonlinear functions. Furthermore, we demonstrate the validity of applying the obfuscation to quantum asymmetric encryption scheme and rigorously prove that the encryption realized by quantum obfuscation satisfies IND(indistinguishablility)-security. This work provides a positive possibility of quantum obfuscation for quantum nonlinear functions and will complement the theory of both quantum obfuscation and quantum asymmetric encryption.